Формування критичного мислення засобами дитячого фольклору - Левчук, Я. (Народна творчість та етнографія, 2006)
The forming of critical thinking system, embodied in the Ukrainian children's folklore and maternal lyric poetry, is investigated in the research. The children folklore provides the forming of the ability to plan own actions, favours the willingness to analyse evident things in a new way, proposes the wide spectrum of decisions for the search of compromise. The metacognitive monitoring process has been already analysed in several texts. After Diane F. Halpern, all these abilities are the components of critical thinking as an objective and logical thinking, taking into account both own point of view and other ideas, an ability to denyown preconceived estimations.